2014
DOI: 10.5897/jvmah2014.0276
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biosecurity measures on broiler farms in Khartoum, Sudan

Abstract: This study was designed to evaluate the present biosecurity measures in broiler farms in Khartoum and to compare between the biosecurity practices followed in closed system and open system farms. The primary information that included numbers of broiler poultry in each farms, locations in the state and type of farms were obtained from Ministry of Agriculture and Animal Resources, Khartoum. Multi-stage cluster sampling method was used; collection of information was done at different levels (sites, farms and pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
4
4
0
Order By: Relevance
“…During this study, it is found that half of the total farms examined were at a distance between 0.5-1km and complained from frequent passage of neighboring farms vehicles via near public road. The same finding was reported by Mahmoud et al [17] who found that the distance to the nearest farm was more than 500 m in 75.5% of the respondents of the surveyed farms. According to [18], there was no set distance that will uniformly eliminate the risk of disease transfer.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…During this study, it is found that half of the total farms examined were at a distance between 0.5-1km and complained from frequent passage of neighboring farms vehicles via near public road. The same finding was reported by Mahmoud et al [17] who found that the distance to the nearest farm was more than 500 m in 75.5% of the respondents of the surveyed farms. According to [18], there was no set distance that will uniformly eliminate the risk of disease transfer.…”
Section: Discussionsupporting
confidence: 88%
“…However, low restriction to protective wearing beside hands washing and disinfecting after removing dead birds were observed or contact with waste. The same findings were also noted by [17] who found that 68.9% of farmers separated sick birds from health birds and 95.5% of respondents used burring for disposable of dead birds and just two farms (4.4%) left dead birds thrown. In contrast, [21] conducted a study evaluating the disposal of manure and dead birds in poultry farms in Khartoum State, Sudan and they found that 77.03% of farms under study disposed their manure and dead birds improperly.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Across the world, including Sudan, new methods and technologies for transforming poultry production from traditional farming into modern industry attaining higher production are being widely adopted [4]. The total poultry meat production per year in Sudan reached 90 million tons [5]. With the increase of consumer awareness of the nutritive value of poultry products, increase in production and the decline in prices relative to the higher prices of other types of animal proteins, the demand for healthy poultry products is increasing rapidly [6].…”
Section: Introductionmentioning
confidence: 99%
“…were isolated from the samples examined. Another study also revealed high microbial level of pathogenic bacteria on poultry carcasses which reflected poor hygienic management concluding that it is far away from international standards [5], [19].…”
Section: Introductionmentioning
confidence: 99%